2010
DOI: 10.1073/pnas.0913292107
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of attention and consciousness on afterimages

Abstract: The brain's ability to handle sensory information is influenced by both selective attention and consciousness. There is no consensus on the exact relationship between these two processes and whether they are distinct. So far, no experiment has simultaneously manipulated both. We carried out a full factorial 2 × 2 study of the simultaneous influences of attention and consciousness (as assayed by visibility) on perception, correcting for possible concurrent changes in attention and consciousness. We investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
132
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(144 citation statements)
references
References 80 publications
8
132
3
1
Order By: Relevance
“…This is unlikely. For one thing, there is now ample evidence of a double dissociation between attention and mental states' being conscious [69][70][71][72][73]; attention occurs in connection with states that are not conscious, and is absent with many states that are conscious. And it is in any case subjectively implausible that attention is needed for states to be conscious; many peripheral visual states are conscious but seemingly unattended.…”
Section: Higher-order Misrepresentationmentioning
confidence: 99%
“…This is unlikely. For one thing, there is now ample evidence of a double dissociation between attention and mental states' being conscious [69][70][71][72][73]; attention occurs in connection with states that are not conscious, and is absent with many states that are conscious. And it is in any case subjectively implausible that attention is needed for states to be conscious; many peripheral visual states are conscious but seemingly unattended.…”
Section: Higher-order Misrepresentationmentioning
confidence: 99%
“…Using a design very similar to that of van Boxtel et al [23], Watanabe et al [53] also independently manipulated attention and stimulus awareness, now using fMRI to measure cortical activity in human V1. In this case, the design led to the conclusion that modulations of V1 activity that co-occur with absence of awareness are entirely due to inattention, not unawareness.…”
Section: Concern 2: Distinguishing Abolished Awareness From Inattentionmentioning
confidence: 99%
“…The approach, in other words, entails a two-by-two design where attention and suppression are both varied, with the intention of separately assessing the effects of each factor. The approach was first developed by van Boxtel et al [23] in a study that measured negative afterimages, a psychophysical marker of neuronal adaptation. This study demonstrated that afterimages were less persistent after viewing an adapter suppressed in binocular rivalry than after viewing a visible adapter (confirming [19,20]), yet more persistent after attending away from the adapter than after attending toward it (consistent with [54,55]).…”
Section: Concern 2: Distinguishing Abolished Awareness From Inattentionmentioning
confidence: 99%
“…Indeed, I have vehemently argued for such a two-way distinction (Koch & Tsuchiya, 2007). It would be interesting to see whether their theory can explain the remarkable experimental finding that attention and consciousness can sometimes have opposing effects (van Boxtel, Tsuchiya, & Koch, 2010).…”
Section: Marco Iacobonimentioning
confidence: 99%